School Operational Funding to Support School Activities - Ahmad, Ahmad; Mohd. Tahir, Lokman (International Journal of Evaluation and Research in Education (IJERE), 2014)
School Operational Funding is a grant from Central Government with a popular name, BOS. Government of South Sulawesi Province collaborates with Government of Makassar District to exploit free education, and Education Support Operational Funding (BOPP) is from government of Makassar District into schools in order to support the success of teaching and learning process. This study aims to analyze the usage of operational School Funding in State Junior High School in Makassar South Sulawesi, Indonesia. This qualitative study used a case study approach with involved semi structured interview, document analysis, and open ended questionnaire. In semi structured interview, it was involved 15 respondents from school management members (5 school headmasters, 5 teachers, and 5 school committee members), and also involved 4 respondents from non-school management members (2 staffs of Education Office of Makassar District and 2 staffs of Education Office of South Sulawesi Province). Therefore, it involved 253 respondents to complete questionnaire (32 headmasters, 172 teachers and 49 school committee members). Data were analyzed by using Nvivo program. The study found that the usage of BOS funding in Junior High School (SMP) in Makassar isn’t maximized in teaching and learning process as its main goal. The funding is still used to finance the implementation of School Based Management Programs. Furthermore, the usage of free education program funding and BOPP isn’t clear. Constructing Planning of School Work and Finance (RKAS) and managing the school operational funding do not involve teachers and school committee members so that its usage is not effective.DOI: http://dx.doi.org/10.11591/ijere.v3i1.5893